2019
DOI: 10.3390/su11154137
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Negotiations in a Self-Organized Grassroots-Led Food Network: The Case of REKO in Finland

Abstract: Self-organization is a term that is increasingly used to describe how engaged citizens come together to create sustainable food systems at the local community level. Yet, there is a lack of understanding of what this self-organizing activity actually means. While previous literature has addressed self-organization as an outcome of building consensus and a collective intentionality shared by the members of a group, we focus on the complex social processes involved when people with a diverse set of interests and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Much of the research on community self-organisation with respect to food systems has focused on understanding the social processes in the emergence of grassroots-led food production and consumption networks [43], community-led alternative food initiatives [44][45][46], community supported agriculture, energy transition [42], urban planning [47], and social movements [48]. These studies focus on identifying principles of self-organisation in the organisational structure, understanding the motivations behind self-organisation, the features of self-organisation, how self-organisation manifests itself in practice, or the agency of individuals and communities that lead to successful self-organising or, in contrast, that undermine the process [43,[49][50][51].…”
Section: Community Self-organisation From a Social-ecological Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Much of the research on community self-organisation with respect to food systems has focused on understanding the social processes in the emergence of grassroots-led food production and consumption networks [43], community-led alternative food initiatives [44][45][46], community supported agriculture, energy transition [42], urban planning [47], and social movements [48]. These studies focus on identifying principles of self-organisation in the organisational structure, understanding the motivations behind self-organisation, the features of self-organisation, how self-organisation manifests itself in practice, or the agency of individuals and communities that lead to successful self-organising or, in contrast, that undermine the process [43,[49][50][51].…”
Section: Community Self-organisation From a Social-ecological Perspectivementioning
confidence: 99%
“…Context is therefore understood as playing an important role in shaping the 'actual practices, ecologies, and materialities involved in the production, distribution, and consumption of food' [50]. It has been shown that at the core of self-organising behaviour can lie a 'self-emerging awareness' of individuals sharing a specific context [43] and "collective intentionality" [54] (p. 234). The context, most often used in understanding the emergence of self-organising behaviour or action, is in terms of ecological, technological, economic, and institutional factors [43].…”
Section: Community Self-organisation From a Social-ecological Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Besides the physical distance, main elements in defining local food are the limited quantities characteristic for smallholders, the environmentally The REKO model of alternative food network (AFN) is a suitable example of applying the principles of sustainable marketing. Founded in Finland in 2013 (Ehrnström-Fuentes & Leipämaa-Leskinen, 2019), it is a face-to-face short food supply chain, where a customer buys food products in immediate personal contact with the manufacturer, a direct relation which assures authenticity and trust (Renting & Marsden & Banks, 2003) in the commercial interaction. The name is an abbreviation of the Swedish "Rejäl Konsumtion", meaning "Fair Consumption" (Ehrnström-Fuentes & Leipämaa-Leskinen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Founded in Finland in 2013 (Ehrnström-Fuentes & Leipämaa-Leskinen, 2019), it is a face-to-face short food supply chain, where a customer buys food products in immediate personal contact with the manufacturer, a direct relation which assures authenticity and trust (Renting & Marsden & Banks, 2003) in the commercial interaction. The name is an abbreviation of the Swedish "Rejäl Konsumtion", meaning "Fair Consumption" (Ehrnström-Fuentes & Leipämaa-Leskinen, 2019). The REKO local food groups connect producers and consumers and facilitate consumers' access to locally produced food at regular intervals, without the intervention of any middleman.…”
Section: Introductionmentioning
confidence: 99%